PRODUK UNGGULAN DAN NILAI PAD: KASUS DI KAB. SUKOHARJO, JAWA TENGAH - - Soetarto; Agus Muqorobin; - Mabruroh (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2011)
A superior product is one of the largest potency for a region in decentralization era so that it cancompete with another region. A limited comparative superiority and a less low opportunity of a region tofind the superiority implicitly drive it for raising a potential comparative superiority. Thus, this superioritymust be developed in the region, for generating more regional incomes (PAD) in particular. As one of thepotential regions in Central Java, Sukoharjo Regency possesses a competitive superiority value, superiorproducts of IKM. Referring to the data of Industrial and Commercial Department and results of AHP dataanalysis, it could be concluded that the superior products of Sukoharjo Regency covered rattan, guitar,furniture and graphics and convention.